Histo-Pathological Evaluation of Gingival Changes in Patients Undergoing Orthodontic Treatment - Farhan Ali, Zubair Ahmed, Suman Muhammad Wazir, Usman Yousaf, Abid Hussain Kanju, Taimur Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To evaluate histopathological alterations in gingival tissue, particularly chronic inflammatory changes and any signs of epithelial dysplasia, in patients undergoing fixed orthodontic treatment. Methods: This cross-sectional study included 71 patients receiving fixed orthodontic therapy at a dental teaching hospital. Gingival tissue biopsies were collected from areas of clinical inflammation. Histological assessment included analysis of epithelial hyperplasia, inflammatory cell infiltration, fibrosis, vascular changes, and dysplasia. Data were analyzed using SPSS, and associations were examined with chi-square tests. Results: Chronic inflammatory features were commonly observed. Epithelial hyperplasia was present in 70.4% of samples, while severe inflammatory infiltrates were seen in 52.1%. Fibrosis, hyperkeratosis, and vascular proliferation were also frequent findings. Importantly, no epithelial dysplasia was identified. A significant association was noted between duration of treatment and severity of inflammation (p = 0.018). Conclusion: Fixed orthodontic appliances are associated with significant chronic gingival inflammation and epithelial remodeling. However, no evidence of precancerous epithelial dysplasia was observed. Regular monitoring and improved oral hygiene practices are recommended to minimize periodontal complications during orthodontic care. Keywords: Orthodontic treatment, gingival inflammation, epithelial hyperplasia, epithelial dysplasia, histopathology, fixed appliances, chronic inflammation.